2011
DOI: 10.1002/pola.25035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of azide‐functionalized nanoparticles by microemulsion polymerization and surface modification by click chemistry in aqueous medium

Abstract: Stable translucent aqueous suspensions of azide‐functionalized cross‐linked nanoparticles (NPs), with diameters in the 15–20 nm range, were prepared using two synthetic approaches. Copolymerization of azidomethylstyrene (VBN3), styrene, and divinylbenzene in various oil‐in‐water microemulsions led to NPs with modulable azide contents (0.53–0.78 mmol/g) and surface over volume distributions. Surface modifications of reactive NPs bearing chlorobenzyl groups, produced by microemulsion copolymerization of vinylben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 78 publications
0
40
0
Order By: Relevance
“…The dyes have been embedded into NPs either during polymerization or after particle formation through swelling procedures . Moreover, covalent linkage to reactive groups inside and on the particle surface has also been performed …”
Section: Synthesis Of Dye‐loaded Polymer Npsmentioning
confidence: 99%
“…The dyes have been embedded into NPs either during polymerization or after particle formation through swelling procedures . Moreover, covalent linkage to reactive groups inside and on the particle surface has also been performed …”
Section: Synthesis Of Dye‐loaded Polymer Npsmentioning
confidence: 99%
“…Recently, it was shown that the yield for surface modifications of azide-functionalised nanoparticles with alkyne modified fluorescein by Cu-catalysed click chemistry was dependent on the polymerisation process, surfactants used and accessible azide groups. 28 Furthermore, the 40 catalysts components caused extensive particle aggregation or even decomposition. 29 In addition, oxidation of biological substrates was also observed with Cu-catalysed click chemistry due to hydrogen peroxide and superoxide radical produced by copper ion mediated catalytic oxidation of sodium ascorbate by 45 molecular oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Many new methods have been employed to prepare polymer particles with a welldefined size, e.g., dispersion polymerization (1, 2), emulsion polymerization (3,4), miniemulsion polymerization (5,6), microemulsion (7,8), etc. Among them, dispersion polymerization is a more attractive alternative for the synthesis of dispersed polymeric particles of micron size in a single step.…”
Section: Introductionmentioning
confidence: 99%